Walka z analfabetyzmem w Polsce Ludowej (na przykładzie wybranych dokumentów Ministerstwa Oświaty oraz Biura Pełnomocnika Rządu do Walki z Analfabetyzmem z lat 1949−1951) - Budnik, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The subject of this article is combating adult illiteracy in the People’s Republic of Poland. The existing knowledge concerning the topic has been supplemented with the analysis of the archival documents, currently being in possession of the Central Archives of Modern Records in Warsaw. It describes how illiterates were recognised in the society, in what way they were encouraged to train new skills and how attending the courses was made possible for them. The analysed documents include censors’ reviews of manuals, press articles, letters wrote by former illiterates and other valuable records. The communists were combating illiteracy not only in the name of the social progress, but mostly motivated by their quest to broaden the possibilities of ideological indoctrination – during the courses organised for illiterates and later on. This is why the selection of manuals and other publications addressed to former illiterates was propagandist. The strategic importance of the matter was expressed by Vladimir Lenin himself: “Socialism cannot be built by illiterates” (W. Ozga, Education in the six-year-plan and the revolutionary changes of the society and economics in the People’s Republic of Poland. Warsaw 1951, p. 124).